PEMANFAATAN LIMBAH CANGKANG KERANG SIMPING (Amusium pleuronectes) DALAM PEMBUATAN COOKIES KAYA KALSIUM - Tri Winarni Agustini; A Suhaeli Fahmi; Ita Widowati; Agus Sarwono (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2011)
Asian moon scallop (Amusium pleuronectes) eggshell contain minerals expecially calcium which is needed by human. But the scallop eggshell waste have not yet been optimally used in food technologies. This research was aimed to  nd out the effect of addition of scallop shell meal to the qualities of cookies product. The process to extract calcium was done by hydrolysis of protein using acid solution (HCl). The threatments implemented are different concentration of Asian moon scallop eggshell meal of 0%, 5% and 7.5% into cookies dough. Research result showed that increasing on concentration of Asian moon scallop eggshell meal gave highly signi cant effect(α 0.01) to moisture, ash, fat, protein, calcium, phophorus and hardness of cookies. However, it gave no signi cant effect (α 0.01) to hedonic test. The addition of Asian moon scallop eggshell meal of 7.5% concentration resulted in highest calcium content (6.57%), phosphorus content (1.58%), ash content (6.95%), carbohydrate content (52.31%) and hardness of cookies (1.06 KgF). Based on hedonic test the addition of asian moon scallop eggshell meal of 5% concentration was the most acceptable by panelist.Keyword : Asian moon scallop (Amusium pleuronectes) eggshell meal; calcium; phosphorus; cookies